Parásitos en aguas del arroyo Naposta, aguas de recreación y de consumo en la ciudad de Bahia Blanca (provincia de Buenos Aires, Argentina) - Costamagna, Sixto Raúl (2005)
The aim of the present study was to detect the presence of sanitarily important parasites in the water from Arroyo Napostá as well as in the water used for recreational purposes (public swimmingpools) and for consumption in the city of Bahía Blanca, province of Buenos Aires, Argentina. To this end, 24,000 liters of water from different sectors of Arroyo Napostá; 2,000 liters of water from each of the three public swimming-pools of Bahía Blanca; and 8,000 liters of water for consumption were collected using polypropylene spun cartridge filters with a 1 μm porosity (Cuno Micro Wind II). Further processing was conducted following Madore´s technique (1987) modified by Pezzani (2000). Detection of Cryptosporidium sp. Giardia sp. was carried out via direct immunofluorescence. Our study confirmed the presence of the following parasites in the areas of study: Hymenolepis diminuta eggs, Giardia sp cysts, Toxocara sp eggs, Entamoeba sp cysts, Endolimax sp cysts, Nematode larvae, Trichostrongylus sp eggs, Ascaris sp eggs, and Cryptosporidium sp cysts in the water from Arroyo Napostá; Hymenolepis diminuta eggs, Giardia sp cysts, Toxocara sp eggs, Entamoeba sp cysts, Endolimax sp cysts, Nematode larvae, Trichostrongylus sp eggs, Ascaris sp in the water from swimmingpools; and Cryptosporidium sp in the water for consumption. The results from the present study urge sanitary authorities from the city of Bahía Blanca to take measures in order to prevent not only humans but also animals from getting in contact with these waters which are contaminated and dangerous to health.